Robust LFC in a smart grid with wind power penetration by coordinated V2G control and frequency controller - Vachirasricirikul, Sitthidet; Ngamroo, Issarachai (My University, 2014)
In the smart grid, the large scale wind power penetration tends to expand vastly. Nevertheless, due to the intermittent power generation from wind, this may cause a problem of large frequency fluctuation when the load-frequency control (LFC) capacity is not enough to compensate the unbalance of generation and load demand. Also, in the future transport sector, the plug-in hybrid electric vehicle (PHEV) is widely expected for driving in the customer side. Generally, the power of PHEV is charged by plugging into the home outlets as the dispersed battery energy storages. Therefore, the vehicle-to-grid (V2G) power control can be applied to compensate for the inadequate LFC capacity. This paper focuses on the new coordinated V2G control and conventional frequency controller for robust LFC in the smart grid with large wind farms. The battery state-of-charge (SOC) is controlled by the optimized SOC deviation control. The structure of frequency controller is a proportional integral (PI) with a single input. To enhance the robust performance and robust stability against the system uncertainties, the PI controller parameters and the SOC deviation are optimized simultaneously by the particle swarm optimization based on the fixed structure mixed H2/H\infty control. Simulation results show the superior robustness and control effect of the proposed coordinated controllers over the compared controllers. © 2013 IEEE.
Keywords: Battery state-of-charge; mixed H2/H \infty control; particle swarm optimization; plug-in hybrid electric vehicle; smart grid; vehicle-to-grid